Pengaruh Minat Investasi Terhadap Keputusan Investasi Pada Pt. Global Kapital Investama Berjangka Pekanbaru - Maswir, Mulyadi (Eko dan Bisnis: Riau Economic and Business Review, 2022)
This study aims to determine the effect of investment interest on investment decisions at PT. Global Kapital Investama Futures Pekanbaru. This research method uses quantitative methods with a descriptive approach. Data collection techniques using questionnaires, interviews and documentation. The sampling technique was purposive sampling with predetermined criteria with a total of 83 samples. The data analysis technique used the t test and the coefficient of determination. The results of this study indicate that investment interest has an effect on investment decisions at PT. Global Kapital Investama Futures Pekanbaru, which is known that the value of t count is greater than t table (34.528 > 1.667) and the significance value is less than 0.05 (0.000 < 0.05). So it can be concluded that there is an influence between investment interest on investment decisions at PT. Global Kapital Investama Futures. That is, the higher the investment interest of a customer in investing, the higher the decision to invest, and vice versa.